Bad sleep?: Don't blame the moon! : A population-based study - Haba-Rubio, José; Kühner, Christine (Sleep medicine, 2015)
The aim of this study was to evaluate if there is a significant effect of lunar phases on subjective and objective sleep variables in the general population. A total of 2125 individuals (51.2% women, age 58.8 ± 11.2 years) participating in a population-based cohort study underwent a complete polysomnography (PSG) at home. Subjective sleep quality was evaluated by a self-rating scale. Sleep electroencephalography (EEG) spectral analysis was performed in 759 participants without significant sleep disorders. Salivary cortisol levels were assessed at awakening, 30 min after awakening, at 11 am, and at 8 pm. Lunar phases were grouped into full moon (FM), waxing/waning moon (WM), and new moon (NM). Overall, there was no significant difference between lunar phases with regard to subjective sleep quality. We found only a nonsignificant (p = 0.08) trend toward a better sleep quality during the NM phase. Objective sleep duration was not different between phases (FM: 398 ± 3 min, WM: 402 ± 3 min, NM: 403 ± 3 min; p = 0.31). No difference was found with regard to other PSG-derived parameters, EEG spectral analysis, or in diurnal cortisol levels. When considering only subjects with apnea/hypopnea index of <15/h and periodic leg movements index of <15/h, we found a trend toward shorter total sleep time during FM (FM: 402 ± 4, WM: 407 ± 4, NM: 415 ± 4 min; p = 0.06) and shorter-stage N2 duration (FM: 178 ± 3, WM: 182 ± 3, NM: 188 ± 3 min; p = 0.05). Our large population-based study provides no evidence of a significant effect of lunar phases on human sleep.